Cardiovascular Disease Risk Profiles in Indonesian Athletes - Achmad, Bayu Fandhi; Alim, Syahirul; Kusumawati, Happy Indah; Fitriawan, Akbar Satria; Kurniawan, Dedi; Kafil, Raisa Farida (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Notwithstanding how physical exercise lessens cardiovascular and all-cause mortality, young and active athletes might have cardiovascular risk factors or fundamental cardiovascular diseases (CVDs), putting them at increased risk for sudden cardiac death during times of strenuous exercise. AIM: The study aimed to assess the cardiovascular risk profile possessed by Indonesian athletes. METHODS: This research was a quantitative study using a cross-sectional design, involving 234 Indonesian athletes (163 men and 71 women) from three sports, including football, basketball, and swimming. Data were collected between December 2020 to March 2021 using the Jakarta Cardiovascular Risk Score instrument adapted from the Framingham risk score. Descriptive statistics were utilized to dissect data information for frequency distribution, percentage, mean, and standard deviation. RESULTS: Most of the participants in this study had excessive weekly exercise duration (more than 255 minutes/week) (n=177 athletes, 75.64%). Twenty-one participants (8.97%) had a higher MAP more than normal, and 51 participants (21.79%) had overweight BMI. In addition, 142 participants (60.68%) had a cardiovascular genetic disease from their parents (family history) and most of the participants also were active smokers (n=150, 64.10%). Based on the Jakarta Cardiovascular Risk Score, the Indonesian athletes who participated in this study had a mean cardiovascular risk of -1.5 (SD= 3.088, min-max= (-7) – 6). Most of the participants had low cardiovascular risk (n= 193, 82.48%). However, some participants had moderate and high cardiovascular risk, 32 (13.67%) and 9 (3.85%), respectively. CONCLUSION: Most of the participants had low cardiovascular risk, however some of the participants had moderate and high cardiovascular risk.